Sport and neoliberalism : politics, consumption, and culture - Silk, Michael L.; Andrews, David L. (Sporting (Philadelphia, Pa.), 2012)
Offering new approaches to thinking about sports and political ideologies, Sport and Neoliberalism explores the structures, formations, and mechanics of neoliberalism. The editors and contributors to this original and timely volume examine the intersection of sport as a national pastime and also an engine for urban policy-e.g., stadium building-as well as a powerful force for influencing our understanding of the relationship between culture, politics, and identity. Sport and Neoliberalism examines the ways the neoliberal project creates priorities for civic society and how, in effect, it turns many aspects of sport into a vehicle of public governance. From the relationship between sport and the neo-liberal state, through the environmental dimensions of neo-liberal sport, to the political biopolitics of obesity, the essays in this volume explore the ways in which the "logics" of neoliberalism are manifest as powerful public pedagogies through the realm of popular culture. Contributors include: Michael Atkinson, Ted Butryn, C.L. Cole, Norman Denzin, Grant Farred, Jessica Francombe, Caroline Fusco, Michael D. Giardina, Mick Green, Leslie Heywood, Samantha King, Lisa McDermott, Mary G. McDonald, Toby Miller, Mark Montgomery, Joshua I. Newman, Jay Scherer, Kimberly S. Schimmel, and Brian Wilson In the series Sporting, edited by Amy Bass.